(untitled) (Fiep Bulletin - online, 2011)
Guanabara project is a social project executed at the School of Physical Education, Physiotherapy and Occupational Therapy - Federal University of Minas Gerais, in partnership with the Ayrton Senna Institute. It has a systematized technology education through sport for human development as a way of developing the potential of children and young Brazilians, using sport as a strategy of conducting their daily activities. The objective was to check how students are developing skills and values nurtured through the pillars of education. Interviews were conducted with pupils from 7 to 14 years, with young people was conducted a focus group, the interpretation was through content analysis. We conclude that PG is important in creating opportunities, developing the potential of students to enable them to become critical people, autonomous and ethical influencing in the choices for your future life.